Analysis of Factors Related to Operator Selection of Fixed Orthodontic Treatment in Teenagers at SMAN 2 Bondowoso - Risya Azkia; Surartono Dwiatmoko; Hestieyonini Hadnyanawati (Pustaka Kesehatan, 2021)
There is a tendency to use fixed orthodontic appliances, both for straightening teeth and just for styling, causing people not only to do fixed orthodontic treatment to orthodontists but also to general dentist. The purpose of this study was to determine the factors related with the operator selection of fixed orthodontic treatment in teenagers at SMAN 2 Bondowoso. This is an analytical observational study with cross sectional approach. The research subject were 54 students determined by total sampling technique. The research measuring instrument is a questionnaire. Data analysis used univariate and bivariate (chi-square) tests. The results showed that most students (83,3%) chose general dentists and 11.1% students chose orthodontists and the rest chose dental quacks. The results of the chi-square test found that there was a significant association (p<0,05) between the trust factor, the knowledge factor, the parents’ income factor, the accessibility factor, the costs factor, the information factor and the need factor with the selection of fixed orthodontics treatment operatior. It is necessary to Increase knowledge for the community and the availability of information as well as the accesibility of orthodontics so that the correct selection of fixed orthodontic treatment operator in adolescent can be carried out.